Utilizing biomaterial surface properties to improve orthopedic hip implant safety and function in a Safe-by-Design approach - Gielen, Anniek M. C.; Leijten, Niels M.; Balraadjsing, Payal P. S.; Braakhuis, Hedwig M.; Abee, Hannah; Arts, Jacobus J.; van Wezel, Annemarie P.; Oomen, Agnes G.; Beijer, Nick R. M. (Frontiers in Bioengineering and Biotechnology, 2025)
Orthopedic hip implant failure due to adverse events, such as infection, are still a major problem leading to high morbidity and mortality. Over the years, various innovative biomaterials have been investigated to improve safety and functionality of implants. Although novel biomaterials show initial promising results, many fail at the (later) stages of safety testing. We performed a literature review serving as a first step in a Safe-by-Design (SbD) approach. SbD is a strategy which includes safety considerations at early development stages and that streamlines the pre-clinical safety assessment of innovative medical implants. In a SbD approach, the standard safety assessment of medical implants (e.g., ISO10993) is complemented with insights on cell-biomaterial interactions allowing for a better in vivo response prediction. As a first step, these insights are based on existing information from literature. Therefore, in this review, correlations between implant biomaterial surface properties and key biological processes, relevant for the success and safety of titanium hip implants, are investigated. In particular, the influence of biomaterial roughness, wettability and pore size on key biological processes for a hip implant (osseointegration, bacterial adhesion and the immune response) are examined. Although it was found that no ideal combination of properties exist to satisfy the key biological processes simultaneously, the gathered insights provide directions for the development of safe and functional biomaterials. Altogether, an assessment of the different aspects of safety at early development stages within an SbD approach can improve biomaterial functionality and thus safety.